Analysing the seal-fishery conflict in the Baltic Sea and exploring new ways of looking at marine mammal movement data - Jogi, Ornella (2017)
A comprehensive analysis of the available data reveals that there is currently not enough information for making informed management decisions regarding the seal-fishery conflict in the Baltic Sea. Knowledge of hidden and visual damages is limited, which means that the actual cost to the fishing industry from damages is not known. No research has been carried out of the effects of culling seals, which has been one of the main conflict management strategies. As rising seal numbers are probably going to lead to increased damages, then the other main management tool – compensation payments, will not be a viable long-term strategy and does not ensure that coastal fishing industry will survive. I argue that governments should instead concentrate on technical innovations to reduce seal damages, as fish damaged in gear has currently been the main concern for fishermen. In the second part of the thesis, integrated stepselection function was successfully used to look at grey and ringed seal movements on a fine scale, which shows that such a method can be used on marine mammal data to obtain novel information for management. The results showed that both species select for deeper areas compared to what is available within the range of a single step. Previous studies have only shown that seals reside in shallower areas, but as iSSA defines availability more precisely, it was possible to see that although seals are bound to shallower areas due to haul-out sites, they seem to select for deeper water in those areas. Ringed seals had shorter step lengths in deeper areas and when further from coast, whereas grey seals had longer step lengths in deeper areas and away from coast. This might be explained by the difference in water depths that these species use for movement and for feeding. Grey seals selected for steps that were closer to coast and ringed seals selected for steps further from coast. Grey seals had shorter step lengths and directional persistence when slope of the seafloor was steeper, which could show the areas where grey seals prefer to feed and use for directional movement.